PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BAPPEDA KABUPATEN SITUBONDO - Az-Zahra, Irene Elsa Wahyu; Subaida, Ida; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2024)
In the context of development planning, BAPPEDA Situbondo Regency is required to be able to explore and utilize existing potential, solve various problems and challenges, serve or fulfill regional needs. Besides that, we are required to be ready and able to prepare and produce quality planning documents, in order to produce well-planned development that improves the welfare of ASN and the people of Situbondo Regency. The aim of this research is to analyze and test the influence of Compensation, Leadership style and Work environment on ASN Performance through Job satisfaction as an Intervening Variable at BAPPEDA Situbondo Regency. This research is explanatory research. The population in this study was ASN BAPPEDA Situbondo Regency, except for the leader. The sampling technique was determined by non-probability sampling. The data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Compensation has a significant positive effect on Job satisfaction, Leadership style has a significant positive effect on Job satisfaction, Work environment has a positive but not significant effect on Job satisfaction, Compensation has a significant positive effect on ASN Performance, Leadership style has a positive but not significant effect on ASN Performance, Work environment has a positive but not significant effect on ASN Performance, Job satisfaction has a negative but not significant effect on ASN Performance. The results of the indirect influence hypothesis test show that the Compensation variable on ASN Performance through Job satisfaction has a negative but not significant effect, Leadership style on ASN Performance through Job satisfaction has a negative but not significant effect, Work environment on ASN Performance through Job satisfaction has a negative but not significant effect.